Clinical manifestations of meningoencephalitis in HIV-positive patients depending on the etiological factor meningoencephalitis - A. I. Gozhenko; N. A. Gumenyuk; V. S. Goydik (Kazimierz Wielki University, 2015)
Gozhenko A. I., Gumenyuk N. A., Goydik V. S. Особенности клинических проявлений менингоэнцефалитов у ВИЧ-позитивных больных в зависимости от этиологических факторов менингоэнцефалита = Clinical manifestations of meningoencephalitis in HIV-positive patients depending on the etiological factor meningoencephalitis. Journal of Education, Health and Sport. 2015;5(8):103-110. ISSN 2391-8306. DOI 10.5281/zenodo.27359 http://dx.doi.org/10.5281/zenodo.27359 https://pbn.nauka.gov.pl/works/604964 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-a924b9ac-50e1-46c5-bd1e-427ba91fa15d http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A103-110 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 25.07.2015.   ОСОБЕННОСТИ КЛИНИЧЕСКИХ ПРОЯВЛЕНИЙ МЕНИНГОЭНЦЕФАЛИТОВ У ВИЧ-ПОЗИТИВНЫХ БОЛЬНЫХ В ЗАВИСИМОСТИ ОТ ЭТИОЛОГИЧЕСКИХ ФАКТОРОВ МЕНИНГОЭНЦЕФАЛИТА Clinical manifestations of meningoencephalitis in HIV-positive patients depending on the etiological factor meningoencephalitis   А. И. Гоженко, Н. А. Гуменюк, В. С. Гойдык A. I. Gozhenko, N. A. Gumenyuk, V. S. Goydik   Украинский НИИ медицины транспорта, Одесса Ukrainian Research Institute for Medicine of Transport, Odessa, Ukraine   Summary Authors analyzed of hospital charts a resume 132 patients of the Odessa regional center of fight and the prevention of AIDS which was on hospitalization with the diagnosis a meningoencephalitis. Causative agents of a meningoencephalitis were toxoplasmas, a cytomegalovirus, a cryptococcus, a mycobacteria of tuberculosis and not revealed agent. Authors established that irrespective of character of the activator development of a meningoencephalitis in HIV-positive people is characterized by a slow, sluggish current and a monotonous overall clinical picture. Some features connected with character of the activator take place at research of the neurologic status. Authors connect slackness and monotony of process with decrease general reactionary ability of an organism of HIV-infected, and feature of a neurologic picture with additional load on the brain structures to which affinity  causative agents of a meningoencephalitis. Keywords: HIV; meningoencephalitis; etiology; neurological status.     Резюме Авторы проанализировали данные историй болезни 132 больных Одесского областного центра борьбы и профилактики СПИДа, находившихся на стационарном лечении с диагнозом менингоэнцефалит. Возбудителями менингоэнцефалита были токсоплазмы, цитомегаловирус, криптококк, микобактерия туберкулеза. Авторы установили, что независимо от характера возбудителя развитие минингоэнцефалита у ВИЧ-позитивных людей характеризуется медленным, вялым течением и однообразной общей клинической картиной. Некоторые особенности связанные с характером возбудителя имеют место при исследовании неврологического статуса. Вялость и однообразие процесса авторы связывают со снижением общей реакционной способности организма ВИЧ-инфицированных, а особенности неврологической картины с дополнительной нагрузкой на структуры мозга к которым тропны возбудители менингоэнцефалита. Ключевые слова: ВИЧ; менингоэнцефалит; этиология; неврологический статус.